Reindeer talk : Sámi reindeer herding and nature management - Heikkilä, Lydia (fi=Lapin yliopisto|en=University of Lapland|, 2006)
The objects of study are the Wilderness Area Planning Projects in North Western Lapland (Finland). They are examined as cases of implementing nature management in practice adapting the global ideas of environmentalism and national objectives and interests. As a contrast surface are used corresponding cases of nature management in Western Finnmark (Norway). I inspect how the proposed institutional arrangements and argumentations related to nature management are produced and legitimized, and how reindeer herding is taken into consideration. In particular, I search for traces of environ¬mentalism in the ways of constructing nature management. Environmentalism is understood as a kind of epistemological break in the principled ways of conceiving and arranging governance of nature. Related to it, I inspect how the new practices of nature management reframe the local ways of organizing use of nature, and how it is received in the local community. I approach the matter expressly from the perspective of reindeer herding, and inspect how the role and space of reindeer herding as a traditional land use form is affected. In particular, I am concerned about the relationship between the particular way of constructing nature management and the conflicts that pertain to implementing management. In theoretical terms, on the foci are the discourses and institutional practices through which nature is made manageable and managed. I depart from a functional perspective, where discourses and practices are seen mutually intertwined. The discourses are produced in the course of an actual negotiation process, and along with it have material consequences and influences. I explore the main contents of the argumentations of the two parties and seek to find out the most important argumentation principles and contextual understanding that they draw from. The target is to provide new understanding to the current management situation, and perspectives for bringing together the divergent views in practical management issues. Second target is to ...